2021
DOI: 10.3390/vaccines9030251
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric VLPs Based on HIV-1 Gag and a Fusion Rabies Glycoprotein Induce Specific Antibodies against Rabies and Foot-and-Mouth Disease Virus

Abstract: Foot and mouth disease is a livestock acute disease, causing economic losses in affected areas. Currently, control of this disease is performed by mandatory vaccination campaigns using inactivated viral vaccines. In this work, we describe the development of a chimeric VLP-based vaccine candidate for foot-and-mouth disease virus (FMDV), based on the co-expression of the HIV-1 Gag protein and a novel fusion rabies glycoprotein (RVG), which carries in its N-term the FMDV main antigen: the G-H loop. It is demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…In another study, murine polyomavirus cVLPs were manipulated to elicit CD8 + and CD4 + T cells and antibody responses [ 70 ]. The immune response against other cVLPs has also been evaluated recently, specifically for the foot-and-mouth disease virus cVLP vaccine, based on the co-expression of the HIV-1 Gag protein and rabies glycoproteins [ 71 ].…”
Section: Structure Classification Of Vlpsmentioning
confidence: 99%
“…In another study, murine polyomavirus cVLPs were manipulated to elicit CD8 + and CD4 + T cells and antibody responses [ 70 ]. The immune response against other cVLPs has also been evaluated recently, specifically for the foot-and-mouth disease virus cVLP vaccine, based on the co-expression of the HIV-1 Gag protein and rabies glycoproteins [ 71 ].…”
Section: Structure Classification Of Vlpsmentioning
confidence: 99%
“…Previous studies have reported a diameter for Gag-GFP-positive EVs of ∼115 nm as measured by NTA and electron microscopy. 28,33 Discrepancy in size measurement can be explained by variability in instrument sensitivity but also in EV isolation methodology used. In our study, only dual centrifugation at 2500g was used to remove platelets, cellular debris, and aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…Chimeric VLP-based nanovaccines against rabies and FMDV co-expressing a novel fusion rabies glycoprotein have been recently investigated. The authors also optimised VLP production in cell cultures by adding additives and demonstrated the production of specific Abs against both zoonotic diseases in mice, serving as a proof-of-concept recombinant FMDV vaccine candidate which would be easier to produce and safer than currently available vaccines [ 153 ]. The promise of VLPs is highly remarkable against fish pathogenic viruses in which delivery methods are inefficient.…”
Section: Latest Nanovaccine Applications Regarding One Health Relevant Pathogensmentioning
confidence: 99%